X-linked myotubular myopathy in a family of two infant siblings: A case report and review - Amelia Suan-Lin Koe; Yee Yin Tan; Shrenik Vora (Elsevier, 2024)
X-linked myotubular myopathy (XLMTM) is a severe type of congenital skeletal muscle disorder usually presenting at birth requiring extensive resuscitation. While having phenotypic variability, its diagnosis carries a poor prognosis due to high rates of hospitalization and mortality by early infancy. Management of patients with XLMTM should therefore be guided by shared decision-making with parents, considering the severity and progression of the disease, quality of life, and demands on caregivers. We describe a family unit of two half-siblings presenting with the severe neonatal form of XLMTM, with varying prognosis and outcomes. Furthermore, a novel maternally-derived c.343-1G > A variant in intron-5 of the MTM1 gene was identified in this family. Hereby, we propose an algorithm for the management of XLMTM, outlining important considerations during the antenatal and postnatal follow-up period.